ANALYSIS OF LEARNING ACHIEVEMENT OF CHILDREN BROKEN HOME AT PGRI PURWOHARJO HIGH SCHOOL (PHENOMENOLOGY STUDY IN CHILDREN BROKEN HOME) - Harwanti Noviandari; Anggraeni Winarsari; Ahmad Sulthoni (International Jurnal of Education Schoolars, 2021)
Family is the main source or environment that educates children in developing children's potential with love between mother and father. The role of parents as role models and role models for children's psychological and emotional development. Children need direction, control and adequate attention from their parents where parents are one of the most important factors in shaping children's character apart from environmental, social and social factors. On the other hand, if the family cannot function properly, it is possible to form problematic generations that can become a social burden in society. . Disharmony in the family can lead to a broken home, the cause of a broken home can be infidelity, differences in life principles or caused by internal or external problems from both parties. This study aims to determine the impact of the Broken Home on Student Achievement in SMA PGRI Purwoharjo, which includes: 1) How is the impact of the Broken Home on student achievement at SMA Pgri Purwoharjo. 2) How Are The Steps Used To Overcome The Impact Of Broken Home On The Learning Achievement Of High School Students Of Pgri Purwoharjo. This research study is expected to provide learning or information for students, parents, teachers and even schools and the community. The results of the study showed that children with broken home conditions experienced changes both academically and psychologically.